Preface - Čepaitienė, Rasa (Genocidas ir rezistencija, 2024)
The full-scale invasion of Ukraine that Russia launched on 24 February 2022 was an attack on the European security architecture and peaceful cooperation between nations that the international community had created and consolidated after World War II in order to prevent future armed inter-ethnic conflicts on the Old Continent. The Russian Federation, as the successor of one of the winners of this war – the Soviet Union – acquired United Nations Security Council veto power, which it now cynically uses to block the initiatives of other members to condemn Russian aggression against the sovereignty of a neighbouring country and to try to resolve the ongoing Russo-Ukrainian War peacefully. However, when this war began, in addition to the fragile balance of power achieved in post-war Europe being violated and the generally accepted rules of international coexistence being demonstrably broken, the provisions formulated at that time of how war crimes should be assessed in general and who to incriminate as the evil that caused them that were, inter alia, consolidated by pan-European means of history politics, were also attacked.